The conservation of the urban, architectural and historic ensemble of the Saint Joseph Church in Belo Horizonte, Minas Gerais, Brazil - Caldeira, Altino Barbosa (DISEGNARECON, 2012)
The architectural and environmental ensemble of Saint Joseph Church was listed by the Deliberated Council of the District of Belo Horizonte due to its importance as a city’s symbolic reference and it take part of the Urban Ensemble of Afonso Pena Avenue that is known as the axis of the capital of Minas Gerais state. Situations in disagreement with the original architectural style and recent inadequate occupations led the Public Ministry and the City Council demand the parish of Saint Joseph, to propose a Director Plan to solve these questions aiming to protect its most important buildings from unwanted interventions. This study shows how this plan was carried out and how the diagnosis and methodology were used in order to achieve the proposed solutions.